2015
DOI: 10.1182/blood-2015-04-637371
|View full text |Cite
|
Sign up to set email alerts
|

NBS1 is required for macrophage homeostasis and functional activity in mice

Abstract: • Nbs1 is a component of the MRE11 complex, which is a sensor of DNA double-strand breaks and plays a crucial role in the DNA damage response.• In mice with a hypomorphic allele of Nbs1, macrophages exhibit increased senescence and abnormal proliferation and inflammatory responses. , macrophage activation-induced ROS caused increased levels of DNA damage that were associated with defects in proliferation, delayed differentiation, and increased senescence. Furthermore, upon stimulation, Nbs1 ΔB/ΔB macrophages e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 56 publications
1
39
0
Order By: Relevance
“…It has recently been reported that stimulated neutrophils generate a burst of ROS that induce DNA damage signaling in activated neutrophils and macrophages, suppressing cytokine production and inducing apoptosis. If the DNA damage reparative systems are effective cells will survive, otherwise they will become apoptotic and die [35][36][37].…”
Section: Cellular Apoptosis Induction and Regulation Pathwaysmentioning
confidence: 99%
“…It has recently been reported that stimulated neutrophils generate a burst of ROS that induce DNA damage signaling in activated neutrophils and macrophages, suppressing cytokine production and inducing apoptosis. If the DNA damage reparative systems are effective cells will survive, otherwise they will become apoptotic and die [35][36][37].…”
Section: Cellular Apoptosis Induction and Regulation Pathwaysmentioning
confidence: 99%
“…2,3 DNA damage responses also regulate celltype-specific programs, including cell survival and differentiation. [4][5][6] In their study, Harbort et al show that DNA damage signaling is activated by ROS in neutrophils and represses proinflammatory functions. In response to invading pathogens, neutrophils secrete proinflammatory cytokines, which recruit additional neutrophils and other immune cells.…”
mentioning
confidence: 99%
“…4,5 figure). This suggests that the increased inflammation in CGD is, in part, a consequence of the defect in ROS-mediated ATM activation and the associated repression of proinflammatory cytokines.…”
mentioning
confidence: 99%
See 2 more Smart Citations